Transcriptome Analysis of Effects of Folic Acid Supplement on Gene Expression in Liver of Broiler Chickens - Zhang, Yujie; Zhang, Ningbo; Liu, Lin; Wang, Yan; Xing, Jinyi; Li, Xiuling (Frontiers in Veterinary Science, 2021)
Folic acid (FA) is a water-soluble B vitamin, and plays an important role in regulating gene expression and methylation. The liver is the major site of lipid biosynthesis in the chicken. Nevertheless, how gene expression and regulatory networks are affected by FA in liver of broilers are poorly understood. This paper conducted the RNA-seq technology on the liver of broilers under FA challenge investigation. First, 405 differentially expressed genes (DEGs), including 157 significantly upregulated and 248 downregulated, were detected between the control group (C) and the 5 mg FA group (M). Second, 68 upregulated DEGs and 142 downregulated DEGs were determined between C group and 10 mg FA group (H). Third, there were 165 upregulated genes and 179 downregulated genes between M and H groups. Of these DEGs, 903 DEGs were successfully annotated in the public databases. The functional classification based on GO and KEEGG showed that “general function prediction only” represented the largest functional classes, “cell cycle” (C vs M; M vs H), and “neuroactive ligand-receptor interaction” (C vs H) were the highest unique sequences among three groups. SNP analysis indicated that numbers of C, M and H groups were 145450, 146131, and 123004, respectively. Total new predicted alternative splicing events in C, M, and H groups were 9521, 9328, and 8929, respectively. A protein-protein interaction (PPI) network was constructed, and the top 10 hub genes were evaluated among three groups. Finally, ultramicroscopy results showed that FA could reduce lipid droplets in livers from chickens. These findings reveal the effects of FA supplement on gene expression in liver of broilers, which can provide information for understanding the molecular mechanisms of FA regulating liver lipid metabolism.